4th National Meeting of Dental Technicians and Technologists - Niovis Pedro Garro; Estela de los Ángeles Gispert Abreu (Editorial Ciencias Médicas, 2018)
Within the program conceived by the Cuban Society of Stomatology, on the occasion of the VII Symposium "Vision Oral Health," the IV National Meeting of Technicians and Technologists in Stomatology was held on October 17, 2017, at the headquarters of the National Council of Societies Health Scientists in Havana, Cuba, with the participation of delegates from the province of Havana and Mayabeque. The activity was presided over by Dr.C. Orialis Ramos Leliebre, Lic. Niovis Pedro Garro and Lic. Marlene María Macias Travieso. Delegates from almost all the municipalities participated in the event. In the round table developed by Dr. Manuel Vera González, Dr. María del Carmen Álvarez and Dr. Clara Beatriz Sánchez Peraza, the work of the educational project for children and young people with diabetes was presented in a harmonious and chronological way. which highlights the importance of the coexistence project that is carried out and that will soon arrive at its 25th anniversary. On the other hand, in the round table with aspects for the good work in the attention to the pregnant woman and to the early ages of the life, developed by the MSc. Dr. María Rosa Sala Adam, and the young Dr. Maydel Pérez Fuentes and Dr. Yaiset de la Torre Molina, dialogue, participation and was defined as an integrator. The exhibition of the MSc was innovative. Dra. María Regla Rosell Pedroso, Lic. Juana Ivet Aleaga Andino, Lic. Lina Mercedes Miranda and Lic. Marlene María Macias Travieso, on the use of piercing among young people and the local and general complications that it causes for health . All presentations had oral health as a common denominator as part of general health. Attendees participated actively, making presentations, questions and proposals, including: How to bring the educational project for children and youth with diabetes to Bejucal? The convenience of increasing the disclosure of iatrogenesis in the placement and manipulation of piercing through mass media. To improve educational projects it would be favorable to acquire information about the activities promoted by the Pedagogues Association of Cuba and how to join. There was great acceptance of the booklet "Happy Alert," so it was deemed necessary to send this educational material to work in the health departments and schools of the community. The importance of the influence from the health institutions to strengthen the actions in health promotion in the community environment was exposed. The key words of the meeting were: gratitude, joy, love, knowledge, Cubanness and youth, which, without a doubt, will motivate the V National Meeting of Technicians and Technologists in Dentistry that will take place in October 2018.